Two plasmolipins from the black tiger shrimp, Penaeus monodon and their response to virus pathogens - Vatanavicharn, Tipachai; Pongsomboon, Siriporn; Tassanakajon, Anchalee (My University, 2012)
Two isoforms of plasmolipin were initially identified from the black tiger shrimp (Penaeus monodon) EST database and completed using 5' RACE to reveal complete cDNAs of 558. bp (PmPLP1) and 537. bp (PmPLP2) with 87% nucleotide sequence identity. The deduced amino acid sequences contained four-transmembrane domains and showed the highest amino acid identity (49% and 51%, respectively) to the honey bee (Apis mellifera) chemokine-like factor (CKLF), with a very similar hydrophobic pattern to other plasmolipins. Transcripts of PmPLP1 and PmPLP2 were observed in all tested shrimp tissues with the highest expression levels in the gill and epipodite for PmPLP1 and in the hemocytes and antennal gland for PmPLP2. PmPLP1 transcript levels were significantly upregulated in hemocytes at 24 and 72. h post infection (hpi) with yellow head virus (YHV) (7.4- and 14.7- fold, respectively), but only after 72. hpi by white spot syndrome virus (WSSV). In contrast, PmPLP2 was only slightly (but statistically significant) up-regulated with YHV and WSSV. Thus, PmPLPs have the potential to be a part of viral infection mechanism or defense response. This is the first characterization of a plasmolipin gene in crustaceans. © 2012 Elsevier Ltd.
Keywords: Penaeus monodon; Plasmolipin; Proteolipid protein; White spot syndrome virus; Yellow head virus